Unplugged Activities on Machine Learning and Their Evaluation Through Mental States Attribution - Baldoni, Matteo; Baroglio, Cristina; Bucciarelli, Monica; Capecchi, Sara; Castellani, Leonardo; Gandolfi, Elena; Ianì, Francesco; Marengo, Elisa; Micalizio, Roberto (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Theory of mind refers to the attribution of mental states that humans ascribe to other humans or objects (such as computer-based systems). Recently, the attribution of mental states has been investigated toward Artificial Intelligence (AI) as a basic manner to capture people’s engagement toward it, and people’s perception about AI social skills and AI capabilities. In line with this idea, mental state attribution can be used as an indirect measure of students’ understanding of AI functioning, and in particular of the kind of interactions students may have with AI systems. Too often is the case of people using generative AI systems in ways that exceed their actual ways of functioning. In our study, children of age in the range 9-12 were involved in one-shot unplugged activities concerning data and models. The unplugged activities were not aimed at teaching the theory of Machine Learning, but rather they were designed so as to provide awareness on some basic mechanisms and help developing a correct use of tools that are becoming more and more present in everyday life. This paper introduces the activities and reports the results that were achieved.